Exploiting Hermann brain dominance theory in students’ performance / Anis Mardiana Ahmad, Fatin Nuraini Sabidi, Wan Siti Esah Che Hussain - Ahmad, Anis Mardiana; Sabidi, Fatin Nuraini (Institute of Research Management & Innovation (IRMI), 2012)
Brain theory discusses about the function of brain in teaching and learning. Studies by brain theory educationist found that people are divided into left brain, right brain dominance and also whole brain. Educationist has been doing research on this matter to justify the role of brain dominance in education. However, it is not clear about the significant influence of the brain dominance in academic performance especially in the abstract topics such as set theory and logic. This study is carried out purposely to reveal the relationship between the brain dominance and student’s performance in the topics of set theory and logic. This study looked into the gender differences, brain dominance and performance among the Faculty of Computer and Mathematical Sciences Diploma students in UiTM Kedah. Data is collected using an established instrument by Herrmann; The Herrmann Brain Dominance. This study found that there is no significant distinction between those with left and right brain with regard to their performance in the topics on set theory among the mathematics and computer science students. In addition to that, the progresses of male and female students from both courses are equal in terms of their performance. The majority of male students were dominated by the right brain, while female students are usually dominated by the left brain. This finding helped educationist to understand more on the students learning capabilities and design an appropriate teaching strategies and approach to teach the abstract concept topics.